Incidence of Acute Ischemic Stroke in Patients With Anti-Platelet Treatment - Ahmed S. Shabaa; Hasanain A. Al-saffar; Abdullah M. Alghazali; FAWATIM ALI Mohammed; Mariam Abdulrazzaq Ali; Mohammed mohanad Lftah; Mariam ALI Fahad (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Acute ischemic stroke remains a leading cause of mortality and long-term disability worldwide, and antiplatelet therapy is a central strategy for primary and secondary prevention of thrombotic cerebrovascular events. Specific Background: Aspirin and clopidogrel are widely prescribed to reduce platelet aggregation; however, ischemic stroke may still occur despite continued treatment. Knowledge Gap: Data from Al-Muthanna City regarding the incidence of acute ischemic stroke among patients receiving antiplatelet therapy and their associated clinical characteristics are limited. Aims: This study aimed to determine the incidence of acute ischemic stroke in patients receiving antiplatelet therapy and to describe related demographic, anatomical, and treatment characteristics. Results: In this cross-sectional study of 102 patients admitted to Al-Hussain Teaching Hospital between September 2025 and March 2026, the mean age was 67.14 ± 7.80 years, and males constituted the majority of cases. Hypertension was the most common comorbidity. Aspirin was the predominant antiplatelet agent (70.5%), followed by clopidogrel (29.5%). Most patients reported regular medication use (84.3%), and 72.5% had received therapy for more than one year. Stroke lesions were most frequently located in the frontal and parietal lobes. Bleeding complications were uncommon and generally mild. Novelty: This study provides regional evidence that acute ischemic stroke occurs despite sustained antiplatelet therapy and good adherence. Implications: The findings support individualized risk assessment, continuous monitoring, and consideration of adjunctive preventive strategies in high-risk patients. Highlights: • Acute ischemic stroke was documented in patients receiving long-term antiplatelet treatment.• Aspirin was the most frequently prescribed agent, with high reported adherence.• Frontal and parietal lobes were the most common sites, and bleeding events were infrequent. Keywords: Acute Ischemic Stroke, Antiplatelet Therapy, Aspirin, Clopidogrel, Stroke Prevention